MOTIVASI KEAKTIFAN MAHASISWA DALAM MENGIKUTI KAJIAN ISLAM DI MASJID ARFA’UNNAS UNIVERSITAS RIAU - Hafiz, Muhammad; ', Risdayati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted at the University of Riau - Pekanbaru. This study aims to determine the motivation of Riau University students in following Islamic studies at the Arfa'unnas Mosque, University of Riau. To find out the driving factors and impact of Riau University students in following Islamic studies at the Arfa'unnas Mosque at UNRI on their academic activities. This study was entitled